Laboratory Manual for Introductory Geology - Deline, Bradley; Harris, Randa; Tefend, Karen (Open textbook library., 2015)
This textbook is a comprehensive lab manual for the core curriculum Introductory Geosciences classes with both informational content and laboratory exercises. Topics include basic laws and theories in Geology, the Earth's interior and plate tectonics, water and climate change, igneous rocks and volcanoes, and earthquakes.